Sociodemographic profile of health workers away during the Covid-19 pandemic in Piauí (Research, Society and Development, 2021)
Covid -19 is a respiratory disease caused by the new coronavirus (SARS-Cov- 2), which. The World Health Organization (WHO) declared, in January 2020, that this disease constitutes a Public Health Emergency of International Importance, with more than 5 million confirmed cases and a high mortality rate. During the pandemic, there were profound changes in working hours, especially for health professionals, who are at the forefront of fighting the coronavirus and started to work overtime, increased the work intensity, consequently, had a longer time of contact with viruses. Thus causing a high rate of infection by workers. These infections are associated with, little knowledge about the virus and its diagnostic, transmission and treatment measures; inadequacy or failures in the precautionary and protection measures against the outbreak; shortage of personal protective equipment (surgical and PFF2 masks and clothing) and infected and asymptomatic individuals who maintained contact with health workers. The importance of this work is to assess the impact of the coronavirus on the health of health workers in this pandemic, to analyze and stratify the number of professionals who have been removed from their work activity because it is contaminated by Covid-19. Thus, all health services need guarantee mechanisms and measures for the protection and promotion of health, since the work of these health workers is essential to face the pandemic.